The experience of using the ‘newsflash approach’ to democratise teaching, learning and assessment at a South African university - Mubangizi, Betty C; O’Brien, Frances (South African Journal of Higher Education, 2016)
In this paper, the use of print media in university curricula is considered, in order to help theorise our practice in higher education in South Africa and elsewhere. Furthermore, the potential contribution of such media to the kind of education to which we aspire, is interrogated. Our reflections are based on an assessment of the use of different media (hard copy or web-based content of newspaper articles) in a third year community development module, at a large contact university in South Africa, over a five year period. The module focused not on academic literacies per se, but on disciplinary content, work-related skills, and the development of critical thinkers and citizens. We considered Bloom’s (amended) taxonomy of learning objectives and activity theory to structure our reflection. It is concluded that the use of popular media can add value to the class learning experience, although there are notable concomitant challenges, which are discussed.